AB0627 Rise-ssc: a double-blind, randomised study evaluating the efficacy and safety of riociguat for the treatment of patients with diffuse cutaneous systemic sclerosis. (15th June 2017) - Khanna, D; Allanore, Y; Denton, C; Matucci-Cerinic, M; Pope, J; Yao, Z; Curram, J; Pena, J de Oliveira; Distler, O
Abstract : Background: Diffuse cutaneous systemic sclerosis (dcSSc) is a severe subtype of SSc, a rare, chronic autoimmune connective tissue disease associated with significant morbidity and mortality, and with reduced quality of life. Currently, there are no approved disease-modifying therapies to treat the vascular and fibrotic damage in patients with dcSSc. Soluble guanylate cyclase stimulators, such as riociguat, target the transforming growth factor beta pathway, inhibiting signalling through non-SMAD pathways. They have been shown to inhibit dermal fibrosis in several animal models and to ameliorate fibrosis of the skin and intestine in bleomycin-induced fibrosis and experimental chronic graft-versus-host disease. 1 These preclinical data suggest that riociguat has vascular and antifibrotic properties that may be beneficial in dcSSc, potentially delaying disease progression. Objectives: RISE-SSc (NCT02283762 ) is an international, multicentre, randomised, double-blind, placebo-controlled, parallel-group, Phase II study to assess the efficacy and safety of treatment with riociguat versus placebo in patients with dcSSc. The primary efficacy endpoint is change in modified Rodnan skin score (mRSS) from baseline to Week 52. Methods: Eligibility criteria include a disease duration of ≤18 months and mRSS of 10–22, parameters identified to be predictors of progression of skin fibrosis. 2 Patients were randomised (1:1) to treatment with riociguat (adjusted up to 2.5 mg tid over the first 10 weeks) or placebo for a total of 52 weeks. The double-blind phase will be followed by an open-label extension phase for up to 6 years where all patients receive riociguat. Results: Study recruitment was completed on 30 Dec 2016 and 121 patients have been randomised. Mean±SD age at inclusion was 50.7±12.3 years (range 18–79) and 76% (n=92) were female. At baseline the mean±SD mRSS was 16.8±3.7 (range 10–22) and disease duration was 8.8±5.5 months (range 0.5–18.5). Almost 70% of the patients tested positive for either anti-SCL-70 (43%) or anti-RNA polymerase III (25%) antibodies, while 32% of patients tested negative for these two antibodies. Swollen and tender joint counts were present in 38 (31.4%) and 51 (42.1%) patients, respectively, while 35 patients (28.9%) had tendon friction rubs. Digital ulcers were present in 15 patients (12.4%) at baseline. Conclusions: RISE-SSc has a unique trial design with a cohort enriched for disease progressors, 2 which is reflected in the baseline characteristics of the randomised patients. Results of the RISE-SSc study will provide data to inform not only the efficacy, safety and tolerability of riociguat treatment in patients with dcSSc, but also the feasibility of a new trial design based on cohort enrichment. References: Khanna D, et al. J Scleroderma Relat Disord 2016;1:186–93. Maurer B, et al. Ann Rheum Dis 2015;74:1124–31. Disclosure of Interest: D. Khanna Grant/research support from: Bayer, BMS, Genentech/Roche, Sanofi-Aventis, NIH K24AR063120, Consultant for: Actelion, Bayer, Covis, Cytori, EMD Serono, Genentech/Roche, Gilead, GSK, Sanofi-Aventis, Y. Allanore Grant/research support from: BMS, Genentech-Roche, Inventiva, Pfizer, Sanofi, Consultant for: Actelion, Bayer, Biogen, Genentech-Roche, Galapagos, Medac, Pfizer, Sanofi, Servier, UCB, C. Denton Grant/research support from: CSL Behring, Bayer, GSK, Inventiva, Consultant for: Actelion, Bayer, GSK, Merck-Serono, Genentech-Roche, Inventiva, Sanofi-Aventis, Boehringer Ingelheim, M. Matucci-Cerinic Grant/research support from: BMS, Pfizer, Actelion, MSD, Lilly, Speakers bureau: Pfizer, BMS, Actelion, Lilly, J. Pope Grant/research support from: Bayer, Merck, Consultant for: BMS, Roche, Bayer, Merck, Z. Yao Employee of: Bayer Healthcare Company Ltd, Beijing, China, J. Curram Shareholder of: Bayer AG, Employee of: Bayer plc, J. de Oliveira Pena Employee of: Bayer US LLC, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Pfizer, Sanofi, Consultant for: 4 D Science, Actelion, Active Biotec, Bayer, BiogenIdec, BMS, Boehringer Ingelheim, ChemomAb, EpiPharm, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, Mepha, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Pfizer, Sanofi, Serodapharm, Sinoxa, Speakers bureau: AbbVie, iQone Healthcare, Mepha